PROPOSED BUSINESS STRATEGY OF BANK ALTIUS TOWARDS BUSINESS EXPANSION TO STATE OWNED ENTERPRISE - Arimbawa, Putu
Since its establishment, Bank Altius has gone through growth and innovation. However, there is a potential topic for investigating its competitive advantage particularly in State Owned Enterprise (“SOE”) market segment. Therefore, this research proposes how Bank Altius increase its competitive advantage in order to gain market share in SOE. This research applies a comprehensive analysis of stakeholders (i.e., external and internal stakeholders) by using several analysis frameworks and in-depth interview, beyond internal and external analysis. This research revealed that the economic recovery stimulus that drives the economy survives during pandemic and intense rivalry drive the bank to find its niche to outperform the stiff competition. This research also found that Bank Altius has the competent person to serve the SOE and strong support from the parent company, moreover Bank Altius maintains a low level of non-performing loan that drives competitive pricing. The identification of internal and external opportunities is necessary to gain SOE market share whereas it demonstrates in leveraging the strong relationship with SOE to do the cross-sell various products and services. Lastly, there are several aspects that require to be improved viz. flexibility, in-depth understanding, competitive pricing, balancing for SOE’s assessment, openness, supportive in good and bad time are determinant factors influencing them to building the banking relationship.